Competitividad de Dorf Ketal Brasil Ltda a partir de la estructura organizacional, su talento humano y la innovación tecnológica de soluciones químicas en el sector hidrocarburo en Colombia (2022)
This paper is a case study, which seeks to determine the competitiveness of Dorf Ketal Brasil Ltda Suc. Colombia in the chemical treatment business line in the hydrocarbon sector. It begins with the identification of the best application organizational structure for the branch based on the Mintzberg structures, where the most adjustable structure for the branch that generates the positive impact on competitiveness is detected and recommended. For this, the strategic planning of the branch is structured, shaping the mission, vision, organizational culture, strategic objectives and policies, which lead to the orientation and direction of the path that the company would need to be competitive in the market.